THE EFFECT OF CONTENT MARKETING AND INFLUENCER ON PURCHASE THE EFFECT OF CONTENT MARKETING AND INFLUENCER ON PURCHASE DECISIONS PRODUCT FASHION AT PLATFORM TIKTOK - Andriano A Abubakar; Sulfi Abdul Haji; Ririn Damayanti (Journal of Management and Islamic Finance, 2024)
The purposes of this research are: To find out and analyze how the partial influence of content marketing and influencer variables on purchasing decisions for fashion products on the Tiktok platform studies on Campus II Unkhair students and to determine the simultaneous influence of content marketing and influencer variables on purchasing decisions fashion products on the tiktok platform studies on Campus II Unkhair students. The number of research samples is 80 respondents and data collection using a questionnaire. The test tool used is multiple linear regression analysis using the statistical package for social scientists (SPSS) as a statistical test tool. The results of the study show that content marketing and influencer variables have a partially positive and significant effect on purchasing decisions. Meanwhile, simultaneously that the variables of content marketing and influencer have a positive and significant effect on purchasing decisions.